Complex causal structures of neighbourhood change: Evidence from a functionalist model and yelp data. (February 2023) - Silver, Daniel; Silva, Thiago H.
Abstract: In this study, we articulate a functional model of neighbourhood change and continuity, adapted from a classical model proposed by Stinchcombe in 1968. We argue this model provides a relatively simple way to capture key aspects of the complex causal structure of neighbourhood change that are implicit in much neighbourhood change research but rarely formulated explicitly. To evaluate the model, we formulate six testable propositions, which we empirically test with large-scale data from Yelp.com . We illustrate our approach with the case of Toronto, but find broad support for all propositions in an analysis of six cities. A conclusion reflects on the value of incorporating functionalist models into neighbourhood research and policy. Highlights: Formulation of a functional model of neighbourhood change and continuity Six hypotheses to test complex causal processes of neighbourhood change Demonstration of how to empirically evaluate the proposed model Large-scale assessment using Yelp.com data for six cities in the US and Canada